2012
DOI: 10.1111/j.1750-3841.2012.02722.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Moisture, Lipids, and Select Amino Acid Blocking Agents on the Formation and Stability of Metastable Radicals in Powdered Soy Proteins

Abstract: Levels of metastable radicals in powdered soy protein products typically range from 10 to 100 times greater than the free radicals in other food protein sources. This current research examines various compositional and treatment parameters that might be used to minimize the content of free radicals in foods containing soy proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Levels of these radicals are initially lower right after the isolated soy protein (ISP) is prepared, and then the level of radicals gradually increases during storage of the powdered protein, especially when exposed to oxygen at 40 °C (Boatright and others ). ISP prepared from defatted soybean flour that had approximately 96% of the native lipids removed, exhibited an initial rate of radical accumulation similar to the control ISP, indicating that the reactions contributing to the formation of metastable radicals in the powdered ISP are not strongly dependent on associated lipids (Boatright and others ). The central singlet EPR signal at g = 2.0049 exhibited a P1/2 power saturation at approximately 2 mW and was located in a manganese EPR signal that was strongest in laboratory‐prepared ISP samples.…”
Section: Introductionmentioning
confidence: 96%
“…Levels of these radicals are initially lower right after the isolated soy protein (ISP) is prepared, and then the level of radicals gradually increases during storage of the powdered protein, especially when exposed to oxygen at 40 °C (Boatright and others ). ISP prepared from defatted soybean flour that had approximately 96% of the native lipids removed, exhibited an initial rate of radical accumulation similar to the control ISP, indicating that the reactions contributing to the formation of metastable radicals in the powdered ISP are not strongly dependent on associated lipids (Boatright and others ). The central singlet EPR signal at g = 2.0049 exhibited a P1/2 power saturation at approximately 2 mW and was located in a manganese EPR signal that was strongest in laboratory‐prepared ISP samples.…”
Section: Introductionmentioning
confidence: 96%
“…Examples of metastable carbon radicals in several different food protein sources have been shown using solid phase electron paramagnetic resonance (EPR) spectroscopy (Boatright, Lei, & Jahan, 2009;Boatright et al, 2008;Fan et al, 2016). In the powdered form, the type and level of metastable radicals in soy proteins, once formed, were reported to be relatively stable over a 2-year period (Boatright, Lei, & Jahan, 2012). Once the powdered food proteins are hydrated, the metastable radicals are released and can catalyze oxidative reactions such as protein carbonylation, fragmentation, dimerization, and cross-linking (Stadtman & Levine, 2003;Zhao, Xiong, & McNear, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, it was previously reported that SPI flours have more carbon-centered radicals than animal protein ingredients such as WPI (Boatright et al, 2008;Boatright et al, 2012;Boatright et al, 2009;Lei et al, 2010). The release of those radicals increased during storage (Boatright et al, 2009) and upon hydration (Boatright et al, 2008).…”
Section: Introductionmentioning
confidence: 99%